A precipitate-free AlCoFeNi eutectic high-entropy alloy with strong strain hardening. (30th October 2021) - Shi, Peijian; Li, Yi; Wen, Yuebo; Li, Yiqi; Wang, Yan; Ren, Weili; Zheng, Tianxiang; Guo, Yifeng; Hou, Long; Shen, Zhe; Jiang, Ying; Peng, Jianchao; et al.
Graphical abstract: Highlights: Developing a bulk cast Al19.25 Co18.86 Fe18.36 Ni43.53 EHEA with lamellar eutectics. The developed as-cast EHEA featuring an extraordinary strain-hardening capability. Uncovering the deformation and fracture mechanisms at multiple length scales. A few slip lines and lattice dislocations appearing in the hard B2 lamellae. But dynamic microstructure refinement is identified in the ductile L12 lamellae. Abstract: Over recent years, eutectic high-entropy alloys (EHEAs) have intrigued substantial research enthusiasms due to their good castability as well as balanced strength–ductility synergy. In this study, a bulk cast Al19.25 Co18.86 Fe18.36 Ni43.53 EHEA is developed with fine in-situ lamellar eutectics. The eutectics comprise alternating ordered face-centered-cubic (L12 ) and ordered body-centered-cubic (B2) phases with semi-coherent interfaces. The resulting microstructure resembles that of most reported as-cast EHEAs, but the B2 lamellae are devoid of nano-precipitates because of the Cr-element removal in current tailored eutectic composition. Surprisingly, the B2 lamellae still feature much higher deformation resistance than the L12 lamellae, so that less lattice defects are detected in the B2 lamellae until the fracture. More interestingly, in the L12 lamellae we identify a dynamic microstructure refinement that correlates to extraordinary strain hardening in tension. The precipitate-free EHEA consequently shows excellent tensile ductility of ∼10 % and high ultimate strength up to ∼956 MPa.